PENERAPAN MODEL PEMBELAJARAN ASSURE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV C SDN 37 PEKANBARU - Ogi Sugiarti; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak:The objectives of this research is to improve learning outcomes IPS academic year 2015/2016. Subjects in this research all fourth grade students of grade IV C SDN 37 Pekanbaru by the number of students as many as 32 students. This research is a classroom action research conducted by two cycles. The results showed after applying the learning model ASSURE in learning IPS learning outcomes increased. This can be evidenced by the value of the acquisition of the activities of teachers in the first cycle of the first meeting with an average of 75% of both categories increased in the first cycle of the second meeting as much as 5,54% to 79,16% with the good category and the second cycle of the first meeting with the price increases both categories increased 83,33% in the second cycle the second meeting as much as 5,26% to 91,66% with very good category. Activities of students in the first cycle of the first meeting with an average of 75% of both categories increased in the first cycle of the second meeting as much as 11,10% to 83,33% with the good category and the second cycle first meeting increased by an average of 87,5% category good and at the second meeting of the second cycle increased by 9,52% to 95,83% with very good category. The results of social studies has increased, before action is ASSURE learning model application data on the basis of the complete score of 6 (18,75%) with an average of 70,78. Which completed the first cycle increased 26 votes (81,25%) with an average of 79,5 and the second cycle increased the complete 29 people (90,62%) with average 87,13 this indicates that the application of ASSURE learning model can improve the results of IPS grade IV C SDN 37 Pekanbaru.Key Words: Learning ASSURE Model, achievement